Bounded Solutions of the Second Order Differential Equation x ?+f(x) x ?+g(x)=u(t) (Baghdad Science Journal, 2015)
In this paper we prove the boundedness of the solutions and their derivatives of the second order ordinary differential equation x ?+f(x) x ?+g(x)=u(t), under certain conditions on f,g and u. Our results are generalization of those given in [1].